Multicomponent Reactions Among Alkyl Isocyanides, sp Reactants, and sp2 Carbon Cages - Li, Yanbang; Kopcha, William P.; Rodriguez-Fortea, Antonio; Zhang, Jianyuan (Synlett, 2022)
We explored the reactivity and substrate scope of the reactions among an alkyl isocyanide, an sp-hybridized reactant (i.e. alkyne or allene), and a carbon cage, as a new approach to functionalize fullerenes and metallofullerenes. This account summarizes the key findings in our recent published work, and some original data for the reaction involving an isocyanide, allenes, and metallofullerene Lu3N@C80.1 Introduction2 Isocyanide-Induced Fullerene/EMF Reactions with Substituted Alkynes3 Isocyanide-Induced Fullerene/EMF Reactions with Substituted Allenes4 Conclusion
Keywords: isocyanide; cluster motion; endohedral; fullerenes; multicomponent reaction